Ark angel - Horowitz, Anthony 1955- (Alex Rider adventures, 2007)
After recovering from a near fatal gunshot wound, teenage spy Alex Rider embarks on a new mission to stop a group of eco-terrorists from sabotaging the launch of the first outer space hotel.